Hubungan Pola Makan dan Aktivitas Fisik dengan Kejadian Hipertensi Usia 40-59 Tahun di Wilayah Kerja Puskesmas Air Dingin - Fitria Alisa; Weny Amelia; Lola Despita sari; Lenni Sastra; Ria Desnita; Vivi Syofia Sapardi; Weri Dwiyanti (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
Age is one of the factors that cannot be changed hypertension. A person who is 40 years old has 3 times the chance of getting hypertension. One of the factors that influence hypertension is diet. The other factors that influence the incidence of hypertension is physical activity. This study aims to determine the relationship between diet and physical activity with the incidence of hypertension aged 40-59 years in the work area of ​​the Air Cold Health Center. This research is descriptive analytic with a cross sectional research design. The technique used is Simple Random Sampling by means of the Lottery Technique. Data processing using Chi-Square test with a sample of 53 respondents. Hypertension incidence (52.8%), poor diet (50.9%), and physical activity (47.2%). There is a relationship between diet and the incidence of hypertension in the work area of ​​the Pukesmas Air Dingin (p value = 0.045) , and there is a relationship between physical activity and the incidence of hypertension in the work area of ​​the Pukesmas Air Dingin (p = 0.001). It is recommended that health workers at the Air Cold Health Center can provide counseling about diet and activities that can result in the incidence of productive age.